Should a retailer sell its own extended warranties or resell those from the manufacturer when confronting supplier encroachment?. Issue 9 (2nd September 2021) - Chai, Junwu; Li, Hengyu; Yan, Wei; Li, Youwei
Abstract: Due to fierce competition in the product market under conditions of supplier encroachment, many brand name retailers, including Sears, Best Buy, and Circuit City, depend on the extended warranty contracts that they sell along with the products. The distribution of extended warranties through an intermediary can be characterized in terms of two basic forms. A large proportion of retailers sell their own extended warranty, whilst others choose to resell the extended warranty provided by upstream agents. Several questions arise from these conditions. How will optimum decisions vary under different strategic choice? Is it profitable for a retailer to engage in selling extended warranties? And finally, which strategy is more profitable for related players? We answer these questions using a game theoretic model where the retailer has the flexibility to choose between offering its own extended warranties (Model ER) or reselling extended warranties provided by a manufacturer (Model EM). Our analysis reveals that it is indeed a profitable business for both parties when the retailer engages in selling extended warranty, irrespective of whether they are owned by the retailer or by the manufacturer. Surprisingly, we find that, when marketing cost of the extended warranty is high, the retailer benefits more from reselling the extended warranty, a strategy that is always beneficial for the manufacturer. Put differently, when marketing cost of the extended warranty is high, reselling extended warranties from the manufacturer can secure Pareto improvements. However, when marketing cost of the extended warranty is not pronounced, a preference confliction arises between both parties: The retailer prefers to sell its own extended warranty, while the manufacturer would be fond of the other one. Extending both models to the case where the manufacturer encroaches into retail market with selling both products and extended warranty reveals that the preference confliction between both parties is quite robust.